2021
DOI: 10.1155/2021/2934082
|View full text |Cite
|
Sign up to set email alerts
|

Diet Quality Indices and Their Correlation with Glycemic Status and Lipid Profile in Patients with Type 2 Diabetes

Abstract: Background. The study aimed to determine the correlation between different diet quality indices and glycemic status and lipid profile in patients with diabetes. Methods. This study was carried out on 235 patients with type 2 diabetes referred to Martyr Motahari Diabetes Clinic of Shiraz city so as to investigate the relationship between glycemic status and lipid profile and the diet quality using Healthy Eating Index (HEI-2010), phytochemical index (PI), and Diet Quality Index-International (DQI_I). Results. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
2
6
0
Order By: Relevance
“…Also, in the total population, higher whole grain intake was associated with an increased level of HDL-C. The findings of the present study are comparable with the results of several previous studies that investigated the possible association of HEI with CVD risk factors and metabolic abnormalities risk (Ziaee et al, 2021;Shah et al, 2010;Saraf-Bank et al, 2017;Monfort-Pires et al, 2014;Huffman et al, 2011;Daneshzad et al, 2019;Asghari et al, 2012a;Zeinalabedini et al, 2023;Firouzabadi et al, 2023;Ahmadijoo et al, 2023); these previous studies have reported the controversial findings on the possible relationship between HEI and the risk of cardiometabolic disorders. Contrary to our results, some studies supported the beneficial role of a diet with a high HEI score in reducing the risk of metabolic disorders; however, similar to our study, some studies did not observe significant results.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Also, in the total population, higher whole grain intake was associated with an increased level of HDL-C. The findings of the present study are comparable with the results of several previous studies that investigated the possible association of HEI with CVD risk factors and metabolic abnormalities risk (Ziaee et al, 2021;Shah et al, 2010;Saraf-Bank et al, 2017;Monfort-Pires et al, 2014;Huffman et al, 2011;Daneshzad et al, 2019;Asghari et al, 2012a;Zeinalabedini et al, 2023;Firouzabadi et al, 2023;Ahmadijoo et al, 2023); these previous studies have reported the controversial findings on the possible relationship between HEI and the risk of cardiometabolic disorders. Contrary to our results, some studies supported the beneficial role of a diet with a high HEI score in reducing the risk of metabolic disorders; however, similar to our study, some studies did not observe significant results.…”
Section: Discussionsupporting
confidence: 88%
“…Daneshzad et al (2019) observed that higher adherence to HEI score was negatively related to mean BS level but did not show any significant association with lipid profile levels or anthropometric factors. Also, a recent cross-sectional study conducted on diabetic patients observed a positive correlation between HEI score and LDL-C level but showed no significant correlation with levels of BS, TGs and HDL-C (Ziaee et al, 2021). However, another study suggested that a higher HEI score can be effective in improving the levels of HDL-C and LDL-C, without a significant relationship with TGs among US adult women (Shah et al, 2010).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…These DQI indices are useful tools for identifying and estimating the quality of diet in different societies with different dietary patterns around the world and their association with chronic nutrition-related diseases such as cancer, diabetes, and fatty liver disease [13,17,19,20]. The relationship between diet quality and BrCa is particularly relevant to study in Iran, due to the increasing rates of BrCa as well as the unique features of the Iranian diet (for example, bulky meals, high intake of refined grains, hydrogenated fats and high percentage of energy intake from carbohydrates),the rapid nutritional transition in this region [21], and high health care costs associated with chronic diseases, especially cancer.…”
Section: Introductionmentioning
confidence: 99%